EVALUASI KESESUAIAN LAHAN TANAMAN JAGUNG (Zea mays L.) PADA LAHAN KERING DI KECAMATAN WAGIR KABUPATEN MALANG - Mei Ridayanti; Mochtar Lutfi Rayes; Christanti Agustina (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Malang Regency has a large area of dry land and currently being developed as a center for food crops, especially corn. Corn production in Malang Regency has not provided high productivity, one of which is in Wagir Regency. This study aims to determine the actual land suitability class, determine the characteristics of the land that affects the productivity of corn, determine the actual productivity class of corn, and develop new land suitability criteria using the boundary line method. This research was conducted in May - September 2019 in Wagir District, Malang, using a physiographic survey method based on the Land Mapping Unit. Soil samples were taken at a depth of 0-120 cm (minipit and drilling) at each observation points (42 points) and analyzed in the laboratory (texture, pH, CEC, C-Organic, BS, N-total, P2O5, Potassium, Ca, Mg, and Na). The determination of land suitability class is carried out using the SPKL (Sistem penilaian kesesuaian lahan) application and the modification of the criteria is carried out using the boundary line method. The results of the land suitability evaluation according to the criteria of Ritung et al. (2011) in Wagir District, Malang Regency, included in class S3 and N, with limiting factors in rainfall, Base Saturation, pH, C-Organic, N-total, P2O5, Potassium, slope and erosion hazard. Stepwise analysis result showed that slope and air temperature determined corn productivity in research area. Boundary lines analysis gave results that modified suitability classified as S3 and N which is the same category as actual suitability classes.